Shattered star - Simon, Charnan (Minneapolis : Darby Creek, 2011)
Cassie is the best singer in Southside High's Glee Club and dreams of being famous. She skips school to try out for a national talent competition, but her hopes sink when she sees the line. Then a talent agent shows up out of nowhere, flattering her and saying she has "the look" he wants. Soon, she is lying and missing rehearsals to meet with him, and he's asking her for more each time. How far will Cassie go for her shot at fame?
Keywords: Singing -- Fiction; Schools -- Fiction; Hispanic Americans -- Fiction